2009
DOI: 10.1111/j.1365-2893.2008.01050.x
|View full text |Cite
|
Sign up to set email alerts
|

FibroScan used in street‐based outreach for drug users is useful for hepatitis C virus screening and management: a prospective study

Abstract: Although hepatitis C virus (HCV) infection prevalence is high among drug users, they do not commonly receive regular care in academic centres. The aim of this prospective study was to assess the influence of FibroScan use on HCV screening and management in street-based outreach. From January 2006 to January 2007, all consecutive drug users were offered noninvasive evaluation of liver fibrosis with FibroScan. After FibroScan, parameters were recorded with a structured, face-to-face questionnaire by outreach wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 44 publications
(45 reference statements)
4
32
0
Order By: Relevance
“…Recently, liver stiffness measurement using FibroScan was evaluated in a street-based outreach for drug users. All consecutive drug users in two street-based outreaches were offered non invasive evaluation of liver fibrosis with a FibroScan [74]. Of the 298 patients included in this study, all of them (100%) accepted liver stiffness assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, liver stiffness measurement using FibroScan was evaluated in a street-based outreach for drug users. All consecutive drug users in two street-based outreaches were offered non invasive evaluation of liver fibrosis with a FibroScan [74]. Of the 298 patients included in this study, all of them (100%) accepted liver stiffness assessment.…”
Section: Resultsmentioning
confidence: 99%
“…In one study of a liver health promotion campaign using transient elastrography-based assessment among PWID in drug and alcohol clinics by Marshall et al, 95% reported that transient elastography was an acceptable method of liver disease assessment (Marshall, this issue). Transient elastography has been shown to be effective for enhancing liver disease screening among PWID attending drug and alcohol clinics in other settings (Foucher et al, 2009;Moessner et al, 2011). Increased community-based liver disease screening using transient elastrography might be one useful strategy for linking PWID in HCV care and triaging those with advanced liver disease who are in most need of immediate treatment.…”
Section: Epidemiology and Prevention Of Hcv Infection Among Pwidmentioning
confidence: 99%
“…FibroScan-based assessment utilizes an ultrasound-based technique to measure liver stiffness, having good diagnostic accuracy for distinguishing cirrhosis from mild disease. In Denmark [62 ] and France [63], FibroScan-based liver assessment at addiction clinics was a feasible strategy to screen for liver disease and HCV.…”
Section: Key Pointsmentioning
confidence: 99%